Pembangunan Game Edukasi Ayo Belajar Rambu-Rambu Lalu Lintas Berbasis Kinect (Studi Kasus TK Kemala Bhayangkari 10 Kota Malang) - Ikrar Amalia Sholekhah; Issa Arwani; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Traffic signs are signs of equipment that described of symbols, numbers, letters, or images and are used as security equipment to road users that they have to compy it. In the year 2017 there has been a traffic incident that reached 6,528 people. Violations happend because of the habit that continues and will put them on the risk of accidents among road users. Therefore it is necessary to learn traffic signs in early learning at the grade of kindergarten education so they will grow into people who orderly traffic. Learning methods can be provided through educational games. Educational Games are the way for someone to find solutions to a problem by making a fun approach. The game will be titled